2015
DOI: 10.3390/pathogens4040739
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epstein-Barr Virus Replication Proteins in Burkitt’s Lymphoma Cells

Abstract: The working model to describe the mechanisms used to replicate the cancer-associated virus Epstein-Barr virus (EBV) is partly derived from comparisons with other members of the Herpes virus family. Many genes within the EBV genome are homologous across the herpes virus family. Published transcriptome data for the EBV genome during its lytic replication cycle show extensive transcription, but the identification of the proteins is limited. We have taken a global proteomics approach to identify viral proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…This premise is supported by data from in vitro studies as well as studies using SCID and humanized mouse models [128,129,130,131]. Similar results have also been reported for Burkitt’s lymphoma [132]. Likewise, HHV-8 associated tumors exhibit low levels of virus reactivation and epidemiological studies support the premise that lytic/abortive-lytic replication is important in the initiation and progression of these tumors [133,134].…”
Section: Herpesviruses Dutpases and Human Diseasesupporting
confidence: 64%
“…This premise is supported by data from in vitro studies as well as studies using SCID and humanized mouse models [128,129,130,131]. Similar results have also been reported for Burkitt’s lymphoma [132]. Likewise, HHV-8 associated tumors exhibit low levels of virus reactivation and epidemiological studies support the premise that lytic/abortive-lytic replication is important in the initiation and progression of these tumors [133,134].…”
Section: Herpesviruses Dutpases and Human Diseasesupporting
confidence: 64%
“…The mechanism remains unknown. BGLF4 was proposed to phosphorylate BGLF5 by an in vitro screen [38], but this finding was not confirmed by mass spectrometry analysis of phosphorylated EBV proteins in Burkitt's lymphoma cells [39]. Also, it is not clear whether the BGLF5 homologs SOX and muSOX are also regulated by the homologous KSHV and MHV68 kinases.…”
Section: Modulation Of Host Shutoff Activity By Other Viral Proteinsmentioning
confidence: 98%
“…All in all, these studies investigating serological lytic EBV markers have emphasized the prominent role importance of the lytic infection in EBV malignancies. Recently, the identification by mass spectrometry of 44 different EBV proteins in Burkitt lymphoma cells undergoing EBV replication has increased the knowledge base on EBV lytic replication, possibly highlighting different targets for future therapeutic strategies [40].…”
Section: Arguments Of the Pathogenic Role Of Lytic Infection In Ebv-amentioning
confidence: 99%
“…Many articles have previously mentioned the existence of the lytic cycle, especially in transplant patients with PTLD. Studies conducted on EBV lytic proteins, especially the IE proteins like ZEBRA, in patients with PTLD or HIV-associated NHL are still scarce, mostly relating to the role of EBV proteins and gene products in neoplastic tissues [18,40,[90][91][92][93][94][95]. It must be pointed out that several authors exploring BZLF1 transcripts in the peripheral blood lymphocytes (PBL) of PTLD patients demonstrated that both a high EBV genome number and strong BZLF1 mRNA expression are sensitive markers of EBV-related PTLD [96].…”
Section: Consequences In Terms Of Diagnosis and Therapymentioning
confidence: 99%